Managing Sustainability Challenges in International Fast Fashion Supply Chains - Repo, Joel (My University, 2025)
The fast fashion industry has grown into a substantial industry in the last two decades and its growth has brought up concerns regarding its environmental, social and economic sustainability. Although sustainability has been a growing theme in business for a long time, research that directly applies sustainability themes to fast fashion is limited. Therefore, this thesis analyses the sustainability issues in international fast fashion supply chains and how they can be managed with sustainable supply chain practices. The aim of this thesis is to analyse the supply chain structure of fast fashion companies using the triple bottom line and sustainable supply chain management frameworks. Through these frameworks the thesis categorizes the issues of the industry as well as provides solutions for different steps of the supply chains to become more sustainable. The fast fashion industry is based on speed, cost-efficiency and global supplier networks. These factors collectively contribute to the unsustainable practices of the industry such as emissions, large quantities of waste and labour exploitation. The application of the sustainable supply chain management framework into the fast fashion industry showed, that addressing these issues required for example cleaner production technologies, route optimization and transparent governance. The findings of the thesis indicate that sustainability and competitiveness can be aligned when fast fashion companies apply SSCM principles into their supply chain management. This however is possible only through a change in managerial decision making and the shift from short-term to long-term thinking in value creation.

Pikamuotiteollisuus on kasvanut merkittävästi viimeisen kahden vuosikymmenen aikana, ja sen kasvu on herättänyt huolta sen ympäristöllisestä, sosiaalisesta ja taloudellisesta kestävyydestä. Vaikka kestävyys on ollut jo pitkään kasvava teema liiketoiminnassa, tutkimusta jossa kestävyyden teemoja sovelletaan suoraan pikamuotiin ja sen toimitusketjuihin on suhteellisen vähän. Näin ollen tässä opinnäytetyössä analysoidaan kansainvälisten pikamuotialan toimitusketjujen kestävyyshaasteita ja sitä, miten niitä voidaan hallita. Tavoitteena on tutkia toimitusketjujen rakennetta käyttämällä triple bottom line sekä sustainable supply chain management teorioita. Näiden teorioiden avulla työssä pyritään luokittelemaan alan kestävyysongelmat ja tarjoamaan ratkaisuja toimitusketjujen eri vaiheiden muuttamiseen kestävämmäksi. Pikamuotiteollisuus perustuu nopeuteen, kustannustehokkuuteen sekä globaaleihin toimittajaverkostoihin. Yhdessä nämä tekijät luovat perustan alan kestämättömyydelle muun muassa päästöjen, suurien jätemäärien ja työvoiman hyväksikäytön muodossa. Soveltamalla sustainable supply chain management teoriaa pikamuodin toimitusketjuihin todettiin, että näiden ongelmien ratkaiseminen edellyttää esimerkiksi puhtaampaa tuotantoa, reittien optimointia sekä läpinäkyvää valvontaa. Tutkimuksen tulokset osoittavat, että kestävyys ja kilpailukyky voidaan sovittaa yhteen, kun pikamuotialalle sovelletaan SSCM periaatteita toimitusketjujen hallinnassa. Tämä kuitenkin edellyttää kokonaisvaltaista muutosta johdon päätöksenteossa sekä siirtymällä arvonluonnissa lyhyen aikavälin ajattelusta pitkän aikavälin ajatteluun.
Keywords: fast fashion, supply chains, sustainability, pikamuoti, toimitusketjut, kestävyys